YEMEN'S POST-ARAB SPRING CONFLICT AND ITS RELATIONSHIP WITH THE ECONOMY, POLITICS, AND SAUDI ARABIA'S INFLUENCE IN THE MIDDLE EAST - Ahmad Masyhur (CMES (Center of Middle Eastern Studies), 2021)
The ongoing war between the Saudi Arabian coalition and the Houthis has had a significant impact. The participation of Saudi Arabia and its coalition in the middle of the Yemen conflict has a pretext to save the democratically elected official government; however, some argue that Saudi Arabia's participation is more of a sectarian issue. The conflict that is still raging in Yemen at this time is considered very interesting to conduct research, in order to find the true background of the participation of Saudi Arabia and its coalition. Is it true that Saudi Arabia's participation was motivated by a desire to save the official government deposed by the Houthis, or is there another motive at work that is in the best interests of Saudi Arabia and its coalition, such as economic, political, or ideological influence?. In this article the researcher uses a qualitative descriptive methodology, qualitative descriptive research in this study will be carried out with several stages including raising a problem, raising research questions, collecting relevant data, analyzing data, and answering research questions. In the investigation, it was found that Saudi Arabia's participation in the Yemeni conflict was inseparable from political, influence and economic interests. Because of the reality that occurred from Saudi Arabia's contradictory attitude toward the Syrian conflict.